(untitled) (Physical Education, Health and Social Sciences, 2025)
Vitamin E, an antioxidant with low water solubility and bioavailability, which can protect the skin from atopic dermatitis and other negative effects of sun radiation by scavenging free radicals. The current work aimed to establish and evaluate a microemulsion-based gel considering transdermal drug delivery of vitamin E, herbal enhancers. clove oil, thymus oil and carbopol 940 used as a gelling agent. Emulsion was developed and it was incorporated in gel base. Formulations were assessed for pH, viscosity, spread ability, conductivity, Homogeneity, drug content, FTIR, XRD, DSC, in-vitro drug release and stability studies were conducted. The formulations characteristics showed improved and stable results. F5 showed higher released rate as compared to others formulations, FTIR and XRD confirmed compatibility and stable physical states, while DSC revealed a suitable formulation. In-vitro studies indicated a sustained drug release profile suitable and fit on first release order for transdermal delivery. It can be concluded that the Vitamin E emulgel demonstrated likely as an effective topical drug delivery system. Its stability, enhanced release, and possible physicochemical characteristics showed a promising option for treating inflammatory skin conditions. It was then thoroughly assessed utilizing methods including FTIR, XRD, SEM, and other common tests for efficacy and quality control. In addition to discussing the emulgel’s potential for topical drug delivery, this report also covers its synthesis, characterisation, and in-vitro release investigations